Science communication in the media and human mobility during the COVID-19 pandemic: a time series and content analysis - Chan, H-Y; Cheung, KC; Erduran, S (Elsevier, 2023)
Objectives The relationship between human mobility and nature of science (NOS) salience in the UK news media was examined. Study design This is a mixed-method study. Methods A time-series NOS salience dataset was established from the content analysis of 1520 news articles related to non-pharmaceutical interventions of COVID-19. Data were taken from articles published between November 2021 and February 2022, which correlates with time period of the change from pandemic to endemic status. Vector autoregressive model fitting with human mobility took place. Results Findings suggest that it was not the number of COVID-19 news articles nor the actual number of cases/deaths, but the specific NOS content that was associated with mobility change during the pandemic. Data indicate a Granger causal negative direction (p < .1) for the effect of the NOS salience represented in the news media on mobility in parks, as well as the effect of scientific practice, scientific knowledge and professional activities communicated in news media on recreational activities and grocery shopping. NOS salience was not associated with the mobility for transit, work or residential locations (p >.1). Conclusions The findings of the study suggest that the ways in which the news media discuss epidemics can influence changes in human mobility. It is therefore essential that public health communicators emphasise the basis of scientific evidence to eliminate potential media bias in health and science communication for the promotion of public health policy. The current study approach, which combines time series and content analysis and utilises an interdisciplinary lens from science communication, could also be adopted to other interdisciplinary health-related topics.